Apprenticeships as the answer to closing the cyber skills gap. Issue 12 (December 2019) - Thompson, Steve
Abstract : It's become increasingly accepted that the cyber security landscape has become more and more hostile in recent years. Even with the most rose-tinted view of the situation, it's clear that both the volume and sophistication of cyberthreats has continued to climb. Companies have become increasingly aware of the damage that cyber attacks can inflict. But this doesn't always translate into the organisation taking the right action. The focus still tends to fall on the technical aspect of security, overlooking the issue of security skills. Apprenticeships can enable organisations to quickly acquire essential capabilities by upskilling their existing personnel and taking on new candidates to train up. With the cyber landscape getting more hostile, now is the time to explore new options for improving defences, says Steve Thompson of Raytheon Professional Services.